Exploring the attitudes of healthcare professionals towards primary healthcare in northwest Syria - Sara Basha; Aravinda Guntupalli; Diana Rayes; Abdulkader Mohammad; Mahmoud Hariri; Lena Basha; Safwan Alchalati; Yamama Bdaiwi; Aula Abbara (BMC Primary Care)
Abstract Background Though primary healthcare (PHC) is an essential component of a robust health system, it remains under-developed and under-resourced in many fragile and conflict affected settings. In Syria, even pre-conflict, the health system had more emphasis on specialist and secondary care with weaker emphasis on PHC. This is beginning to change with investment from donors, international and humanitarian organisations; however, its implementation remains challenging, in part due to negative attitudes towards PHC among both physicians and patients. Our aim is to explore attitudes towards PHC in northwest Syria among relevant stakeholders. Methods A qualitative research design using a contextualist approach was used. Semi-structured interviews were conducted with stakeholders who had experience of the Syrian health system before and after the conflict. Purposive and subsequent snowball sampling were used for recruitment. A topic guide was developed with stakeholders and interviews were conducted using Microsoft Teams. Interviews were transcribed verbatim and translated where appropriate. Inductive thematic analysis was conducted using Nvivo V.12 software. Results Fifteen in-depth interviews were conducted; 7 were female. The main emerging themes and subthemes were: 1. Governance of the health system (subthemes: inadequate communication and coordination; the power of donors; lack of monitoring systems; inadequate health information systems). 2. The observed attitudes of community and patients’ towards primary healthcare (sub-themes: perceived patients’ attitudes towards PHC; importance of building trust with the community; impact of cost on service use). 3. Healthcare workforce and primary healthcare (sub-themes: negative attitudes towards PHC as a specialty; numbers and capabilities of healthcare professionals; changing attitudes towards PHC as a system). Discussion Though there was some evidence that attitudes were changing, there remain prevailing negative attitudes towards PHC, including a reluctance among undergraduates to choose it as a destination specialty. Without further understanding barriers, efforts by donors and humanitarian organisations to implement effective PHC in northwest Syria may flounder.